The Value of ABCD2F Scoring System (ABCD2 Combined with Atrial Fibrillation) to Predict 90-Day Recurrent Brain Stroke - Mostafa Almasi; Nader Hodjati Firoozabadi; Faeze Ghasemi; Mojtaba Chardoli (Neurology Research International)
Background. The ABCD2 score is now identified as a useful clinical prediction rule to determine the risk for stroke in the days following brain ischemic attacks. Aim. The present study aimed to introduce a new scoring system named “ABCD2F” and compare its value with the previous ABCD2 system to predict recurrent ischemic stroke within 90 days of the initial cerebrovascular accident (CVA). Methods. 138 consecutive patients with the final diagnosis of ischemic CVA or TIAs who referred to emergency ward of Rasoul-e-Akram general hospital in Tehran from September 2012 to December 2013 were eligible. By adding a new score in the presence of atrial fibrillation to ABCD2 system, the new scoring system as ABCD2F was introduced and the risk stratification was done again on this new system. Results. The area under the curve for ABCD2 was 0.434 and for ABCD2F it was 0.452 indicating low value of both systems for assessing recurrence of stroke within 90 days of primary event. Multivariable logistic regression analysis showed that none of the baseline factors could predict 90-day recurrent stroke. Conclusion. ABCD2 and/or atrial fibrillation are not good scoring candidates for assessing the risk of recurrent stroke within first 90 days.